Comparison of Aceh cow's performance on different mating systems at BPTU HPT Indrapuri, Aceh Province, Indonesia. Issue 1 (November 2021) - Baliarti, E; Wardani, A S; Prabowo, B W; Meutia, N; Yusmadi,; Marwan,; Bintara, S; Widi, T S M; Ngadiyono, N
Abstract: This research aimed to compare Aceh cow's performance on different mating systems at BPTU HPT Indrapuri, Indonesia. This research uses 202 Aceh cows with varying systems of mating; natural mating (164 cows), and artificial insemination (AI; 38 cows). Cow's performance data included birth weight, postpartum mating, calving interval, weaning weight, Cow Reproduction Index (CRI), and Cow Production Index (CPI), obtained from the recording in 2014-2019 and calculation. This research uses the Oneway Anova test to analyze the cow's performance between mating systems. The results of the cow's performance included birth weight, postpartum mating, calving interval, weaning weight, CRI, and CPI for natural mating system were 14.32±1.41 kg, 265.61±260.0 days, 558, .21±260.07 days, 54.32±19.32 kg, 0.69 calf/cow/year and 37, 48 kg/cow/year respectively, while for AI system were 14, 98±1, 38 kg, 289.34±285, .06 days, 581.94±285.06 days, 59.10±21.83 kg, 0.70 calf/cow/year dan 41.37 kg/kg/cow/year. The results showed that the performance of the Aceh cows with natural mating dan artificial insemination was relatively the same.